Evaluation of recovery, quality and In Vitro nuclear maturation of oocytes obtained from buffalo and bovine ovaries - Leal, L. S. [UNESP]; Moya-Araújo, C. F. [UNESP]; Fernandes, C. B. [UNESP]; Martins, L. R. [UNESP]; Landim-Alvarenga, F. C. [UNESP]; Oba, E. [UNESP] (My University, 2010)
Ovaries of 86 buffaloes and 95 cows were collected from slaughterhouses and transported to the laboratory in saline solution at 36°C. The Cumulus-oocyte complexes (COCs) were recovered by follicular aspiration and only grades I and II COCs were selected and matured in TCM 199 supplemented with 10% fetal calf serum, sodium pyruvate, LH, FSH, estradiol, gentamicin and cysteamin, for 22-24 hours. A total of 714 and 1983 COCs were recovered from buffaloes and cows, respectively. In the buffaloes, the recovery rates of each COCs categories (grade I: 25.9%; grade II: 30.7%; grade III: 10.2%; denuded 18.6% and expanded: 14.6%) were lower than cows (31.8; 30.6; 15.4; 4.5; 17.7%, respectively) according to Mann-Whitney Test (p< 0.05). The percentage of bubaline oocytes that reached metaphase II (63.4% - 242/396) was lower than bovine oocytes (67.8% - 696/1234) under the same laboratory conditions. These differences observed in all analysis realized indicate that each species has peculiar phisiological characteristics.
Keywords: Buffaloes; Cows; In vitro maturation; Oocytes